ANALYSIS OF HEALTH SERVICE QUALITY AND PATIENT VALUES ON REVISIT INTEREST THROUGH OUTPATIENT SATISFACTION AT TAMANAN HEALTH CENTER - Damayanti, Nia; Herlambang, Toni; Mohammad Thamrin (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective : This study aims to analyze the influence of service quality and perceived value on patient satisfaction and revisit intention in the context of outpatient services at Tamanan Community Health Center, Bondowoso. The research further examines the mediating role of patient satisfaction in the relationship between service quality, perceived value, and revisit intention. Understanding these relationships is critical to improving patient-centered care and fostering long-term patient loyalty. Method : This explanatory quantitative study involved 100 respondents, determined through Slovin's formula, with accidental sampling as the sampling technique. Data were collected using questionnaires, observations, and literature review, while both primary and secondary data were utilized. Structural Equation Modeling (SEM) with WarpPLS 8.0 software was employed to test hypotheses and evaluate the relationships between variables, including service quality, perceived value, patient satisfaction, and revisit intention. Results : The findings reveal that service quality and perceived value significantly influence patient satisfaction and revisit intention. Additionally, patient satisfaction serves as a significant mediating variable, strengthening the impact of service quality and perceived value on revisit intention. This indicates that improving service quality dimensions such as reliability, responsiveness, empathy, and ensuring patients perceive high value can enhance satisfaction and loyalty toward healthcare services. Novelty : This study offers a novel perspective by integrating service quality, perceived value, and patient satisfaction as predictors of revisit intention in a primary healthcare setting, particularly in a rural area with unique resource limitations. The findings highlight the importance of tailoring healthcare service strategies to address both tangible and emotional aspects of patient care, providing valuable insights for healthcare providers and policymakers.